Development of a genetic algorithm-based optimization of a small scale dual-axis solar tracking system using nano watt technology - Del Rosario, Jay Robert B. (Animo Repository, 2013)
The solar module will be positioned first in North, East, West or South. Then, the PV array will automatically search and stop at the highest current gained by the solar cell. This will occur every 30 minutes from 0600H up to 1800H. In these positions the values of current, voltage and power were measured. The design focuses on the application of genetic algorithm to capture the maximum power of the solar cells in a small farm setting with fan, incubator, aquarium pump motor and lightning.